TEACHERS’ COMPETENCY AND ITS IMPLICATIONS ON TEACHERS’ RESILIENCE IN FACING SOCIETY 5.0 - Tri Achmad Efendi; Amalia Silwana (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
This research was aimed at exploring current teachers’ competency and its implications on teachers’ readiness in facing society 5.0. As teachers play a pivotal role in helping students facing their future, it becomes mandatory for the teachers to adapt and adjust themselves with the current situation where cutting-edge technology has already influenced our lives in many ways, including education. Teachers nowadays are supposed to equip themselves with at least five competencies: digital literacy, critical thinking, adaptability, and communication. In order to find the answers, the researchers used a descriptive qualitative research design. There were two research instruments employed in this study; questionnaire and interviews. The questionnaire was distributed to thirty-two teachers and three teachers were interviewed. The results showed that of those four competencies, critical thinking is the lowest (81%) and communication is the highest (87.75%). Meanwhile digital literation and adaptability almost shares same result (around 84%). It could be inferred that the critical thinking is the area that needs improvement.